2015
DOI: 10.1186/s12879-015-1316-y
|View full text |Cite
|
Sign up to set email alerts
|

Increases in absenteeism among health care workers in Hong Kong during influenza epidemics, 2004–2009

Abstract: BackgroundAcute respiratory infections (ARI) are a major cause of sickness absenteeism among health care workers (HCWs) and contribute significantly to overall productivity loss particularly during influenza epidemics. The purpose of this study is to quantify the increases in absenteeism during epidemics including the 2009 influenza A(H1N1)pdm09 pandemic.MethodsWe analysed administrative data to determine patterns of sickness absence among HCWs in Hong Kong from January 2004 through December 2009, and used mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 32 publications
1
57
1
1
Order By: Relevance
“…Viral infections (eg, seasonal influenza) have been shown to have a negative impact on worker health and business productivity, through such outcomes as higher sickness absence rates. 7 Furthermore, some of the workplace changes introduced due to the COVID-19 crisis, such as the replacement of face-to-face meetings and conferences with online and virtual assemblies are likely to be maintained. This can lead to positive environmental effects through less traffic congestion and lower carbon emissions from reduced motor vehicle and aircraft travel.…”
Section: Malcolm R Simmentioning
confidence: 99%
“…Viral infections (eg, seasonal influenza) have been shown to have a negative impact on worker health and business productivity, through such outcomes as higher sickness absence rates. 7 Furthermore, some of the workplace changes introduced due to the COVID-19 crisis, such as the replacement of face-to-face meetings and conferences with online and virtual assemblies are likely to be maintained. This can lead to positive environmental effects through less traffic congestion and lower carbon emissions from reduced motor vehicle and aircraft travel.…”
Section: Malcolm R Simmentioning
confidence: 99%
“…The researchers suggested that providing more information might lead to better control of infectious diseases like COVID-19. (Ebrahimi & Nemati, 2020) Another two studies were done in China (Liu et al, 2020) and India (Ip et al, 2015), where both of them targeted the public rather than nurses or healthcare providers. Overall, they found a moderate to adequate awareness related to transmission, symptoms and preventive measures for COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…HCW absenteeism due to influenza increases on average by two days per HCW, both during pandemic and a seasonal virus outbreaks [24]. Ip et al [25] examined overall sickness absences including sick leave due to acute respiratory infection (ARI) for four distinct influenza periods between 2004 and including the 2009 influenza A(H1N1)pdm09 pandemic in Hong Kong. Results showed that the daily HCW absenteeism rate for ARI increased from the pre-pandemic In September 2018 a UK healthcare worker contracted monkeypox after caring for a patient with the disease prior to diagnosis.…”
Section: Workforce Capability and Capacitymentioning
confidence: 99%